VaseLamp Pottery Sdn. Bhd / Muhammad Amir Asyraaf Roslan - Muhammad Amir Asyraaf, Roslan (2020)
VaseLamp Pottery Sdn. Bhd. began in 17 May of 2020 and the first product design was introduce and sell to people in 16 June 2020. This company was established at Kuala Lumpur, Malaysia was owned by Muhammad Amir Asyraaf Bin Roslan. Our company’s concept is producing product according the modern-day design. Our company try to solve people’s problem about how to decorate their home/place with affordable and simple product. VaseLamp Pottery was a private limited company that sold a new type of interior decoration product. As we know, people today are more into a minimalism decoration they always want somethings that multifunctional because most of the people at the city lived in a small house or department that has minimal space. Our company decided to make a multifunctional product that can fit with any modern interior design and have very simple design to it. The product is vaselamp which is a product that combine a vase and a lamp. This product can be use in daylight as decoration and at night as a lamp. My company which is Vaselamp Pottery is a company that focus on vaselamp production with a variety type of design that follow the trend time through time. I decide to make a ceramic/pottery product company as my business because in Malaysia there are not many companies that produce product made of ceramic people are more focus on plastic product and the lack of competitor of this business can increase my market potential. Our company was built in the city so, one of our target markets was based on geographic segmentation which mean we target customer around the place/city. Then, our profitability is highly depending on population of people that lived in the city so, the chances of getting many customers are higher. This is one of our strategy in marketing our company. Next, our company also have a very capable management team that have many experiences in handling and managing the business. So, I can say that our company have very good team and stable financial management that can grow/expand our business in the future.